Photo-induced electron transfer in cu(i) bis-phenanthroline based assemblies. Part I: Chromophore-acceptor diads. Part II: Donor-chromophore-acceptor triads - Lazorski, Megan, author; Elliott, C. Michael, advisor; Shores, Matthew P., committee member; Chen, Eugene, committee member; Bailey, Travis S., committee member; Sites, James R., committee member (Colorado State University. Libraries, 2013)
The photophysical behavior of [Cu(I)P2] (P=2,9-disubstituted-1,10-phenanthroline ligands) in donor-chromophore-acceptor (D-C-A) triads and chromophore-acceptor (C-A) diads is a complex and fascinating area of under developed, yet fundamental, electron transfer chemistry. In metal polypyridyl D-C-A and C-A triads/diads, metal polypyridyl chromophores (C) in which the polypyridyl ligands are covalently linked to acceptor (A) and/or donor (D) moieties, photo-excitation of the chromophore initiates a series of electron transfer events that result in the formation of a charge separated (CS)/charge transfer (CT) state, respectively. The majority of high-performing metal polypyridyl D-C-A/C-A complexes, on which [Cu(I)P2] D-C-A/C-A research is based, incorporate ruthenium (as [Ru(II)L3] where L=polypyridyl ligand) or other rare, expensive, and sometimes toxic metals such as osmium, rhenium and platinum. Although [Ru(II)L3] D-C-A/C-A's have historically set the benchmark for metal polypyridyl D-C-A/C-A performance, it is clear that these complexes are not a practical choice if D-C-A's or C-A's were incorporated into a device for large scale production. However, bisphenanthroline complexes of copper, a much more earth abundant, cheaper and less toxic metal, exhibit very similar photophysical properties to [Ru(II)L3] and have thus gained recognition as promising new materials for D-C-A/C-A triad/diad construction. In order to understand the electron transfer (ET) events occurring in [Cu(I)P2] D-C-A/C-A triads/diads, a complex must be synthesized that is capable of forming a CS with high quantum efficiency (Φcs/ct) and a long CS/CT lifetime (τcs/ct). Therefore, the intent of the research reported herein is to synthesize novel, yet functional heteroleptic [Cu(I)P2] D-C-A/C-A triads/diads and study their fundamental, photo-initiated electron transfer chemistry, specifically the formation of a CS/CT state. Many challenges, which are not present for [Ru(II)L3], make the design and synthesis of [Cu(I)P2] D-C-A/C-A assemblies an art in itself. Therefore, a significant amount of effort was spent on fabricating ligand architectures that (1) are appended with acceptor and/or donor moieties capable of being reduced/oxidized resulting in the formation of a CS/CT, (2) are able to be easily modified so the amount of energy stored in the CS/CT can be tuned, (3) favor the self-assembly of [Cu(I)P2] complexes, (4) are able to facilitate processes that maximize the Φcs/ct. Once the ligands were obtained, the complexation equilibria behavior of these [Cu(I)P2] triads and diads were studied. Despite efforts to design ligand architectures that favor heteroleptic formation, the thermodynamic driving force for heteroleptic D-C-A triad formation is less favor-able than expected. Thus, mixing stoichiometric quantities of D, C and A results in a statistical mixture of C-A, C-D and D-C-A products. Furthermore, since the ligands are labile and will re-arrange to the most thermodynamically stable configuration of products when these complexes are dissolved, isolation of the D-C-A product is impossible. However, recent advances in ligand design have shown promise for resolving this on-going issue. Despite having a mixture of products with the D-C-A, the electron transfer processes of the [Cu(I)P2] D-C-A triads and C-A diads were investigated. Using Transient Absorption (TA) laser spectroscopy, the CT state in the constructed C-A diads and the CS state in the D-C-A triads were detected and the lifetimes were determined. However, it was found that those lifetimes could be modulated to a small degree by solvent in the C-A diads (c.a. 6x longer in polar solvents), and drastically via the application of a magnetic field in D-C-A triads (c.a. 60x longer). The ability to modulate the lifetimes enabled the deconvolution of the effects due to the C-A diad vs D-C-A triad in the statistical product mixtures. Although the response in a magnetic field was a somewhat expected result, as similar effects occur in the [Ru(II)L3 D-C-A/C-A's, the magnitude of change in the lifetime and the quantum efficiency offers new insight into the electron transfer events that occur in the CS/CT formation process for [Cu(I)P2] D-C-A/C-A complexes.
Chromophore-acceptor diads
Donor-chromophore-acceptor triads
Keywords: copper bis-phenanthroline; charge separated state; solar fuels; D-C-A; donor-chromophore-acceptor; chromophore-acceptor diads